WALCOM: Algorithms and Computation 17th International Conference and Workshops, WALCOM 2023, Hsinchu, Taiwan, March 22-24, 2023, Proceedings - Lin, Chun-Cheng.; Lin, Bertrand M. T.; Liotta, Giuseppe (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book constitutes the proceedings of the 17th International Conference and Workshops on Algorithms and Computation, WALCOM 2023, which took place in Hsinchu, Taiwan, in March 2023. The 30 full papers presented together with 2 invited papers were carefully reviewed and selected from 75 submissions. They cover topics such as: computational geometry; string algorithm; optimization; graph algorithm; approximation algorithm; and parameterized complexity.
Invited Talks -- Graph Covers: Where Topology Meets Computer Science, and Simple Means Difficult -- The Family of Fan-planar Graphs -- Computational Geometry -- Minimum Ply Covering of Points with Unit Squares -- Overlapping Edge Unfoldings for Archimedean Solids and (Anti)prisms -- Flipping Plane Spanning Paths -- Away from Each Other -- Piercing Diametral Disks Induced by Edges of Maximum Spanning Tree -- Reflective Guarding a Gallery -- Improved and Generalized Algorithms for Burning a Planar Point Set -- On the Longest Flip Sequence to Untangle Segments in the Plane -- String Algorithm.-Inferring Strings from Position Heaps in Linear Time -- Internal Longest Palindrome Queries in Optimal Time -- Finding the Cyclic Covers of a String -- Efficient Non-isomorphic Graph Enumeration Algorithms for Subclasses of Perfect Graphs -- Optimization -- Better Hardness Results for the Minimum Spanning Tree Congestion Problem -- Energy Efficient Sorting, Selection and Searching -- Reconfiguration of Vertex-disjoint Shortest Paths on Graphs -- k-Transmitter Watchman Routes -- Graph Algorithm -- Splitting Plane Graphs to Outerplanarity -- Certifying Induced Subgraphs in Large Graphs -- Some Algorithmic Results for Eternal Vertex Cover Problem in Graphs -- On the Complexity of Distance-d Independent Set Reconfiguration -- On Star-multi-interval Pairwise Compatibility Graphs -- Parameterized Complexity of Optimizing List Vertex-Coloring through Reconfiguration -- Parameterized Complexity of Path Set Packing -- Approximation Algorithm -- Interweaving Real-Time Jobs with Energy Harvesting to Maximize Throughput -- Recognizing When a Preference System Is Close to Admitting a Master List -- Groups Burning: Analyzing Spreading Processes in Community-based Networks -- Roman k-domination: Hardness, Approximation and Parameterized Results -- Parameterized Complexity -- On the Parameterized Complexity of Compact Set Packing -- Structural Parameterization of Cluster Deletion -- Parity Permutation Pattern Matching.
Keywords: Computer science; Computer science -- Mathematics; Discrete mathematics; Numerical analysis; Algorithms; Computer graphics; Application software; Theory of Computation; Discrete Mathematics in Computer Science; Numerical Analysis; Design and Analysis of Algorithms; Computer Graphics; Computer and Information Systems Applications